Cavitation erosion modelling on a radial divergent test section using RANS - Kevorkijan, Luka (Strojniški vestnik, 2022)
Cavitation is the phenomenon of fluid evaporation in hydraulic systems, which occurs due to a pressure drop below the value of the vapor pressure. For numerical modelling of this generally undesirable phenomenon, which is often associated with material damage (erosion), there are various mathematical vapor transfer models that have been validated in the past. There are different approaches to predicting cavitation erosion, which have mostly been experimental in the past. Recently various numerical models have been developed with the development of numerical simulations. They describe the phenomenon of cavitation erosion based on different theoretical considerations, such as Pressure wave hypothesis, Microjet hypothesis, or a combination of both. In the present paper, an analysis of the Schnerr-Sauer transport cavitation model was used, upgraded with an erosive potential energy model based on pressure wave hypothesis for cavitation erosion prediction. The extended numerical model has been applied to the case of a radial divergent test section in three different mathematical formulations. The results of simulation were compared and validated to experimental work performed by other authors. The study shows that the distribution of surface accumulated energy agrees with the experimental results, although certain differences exist between formulations. The applied method appears to be appropriate for further use, and to be extended to materials response modelling in the future.
Keywords: cavitation; erosion; erosive potential energy; erozija; erozivna potencialna energija; kavitacija; numerical simulation; numerične simulacije